The IBM Lenovo Alliance And The IBM PC Business Sale - Impact To The Global PC Market - Yap, Fwei Keat (2005)
This project paper explores the changes and impacts brought about by the deal between Lenovo and IBM. This paper focuses on the strategic advantages for both companies and also the specific challenges brought about by this marriage of convenience which signifies an affirmation on the commoditization of PC business and the emergence of Chinese company as the world class company of today.